The Implementation of Mass Media Digital Platform in Indonesia - Woro Harkandi Kencana; Meisyanti Meisyanti (Universitas Muhammadiyah Yogyakarta, 2020)
Communication technology in mass media has experienced rapid development. The implementation of digital platforms is carried out by mass media groups in facing competition between media in welcoming society 5.0. This study aims to find out the implementation of digital platforms is carried out by mass media groups in Indonesia through an umbrella perspective. The research method used qualitative approach applying data collection techniques of observation, interviews, and documentation. Interviews were conducted with the person in charge of the digital platform in the media groups. Observations were also taken in the digital platform in the media groups: TransMedia Group, MNC Group, Media Group, Viva Group, Kompas Group, Emtek Group, Jawa Post Group, Netmediatama group, and Mahaka Group. The results of this study show that the forms of the current mass media digital platforms used are websites, online media, applications, and social media. In the infrastructure of media organizations, digital platforms are a form of media group policy in converting technology, content convergence, and economic convergence. Digital platforms have also provided new low-cost income for the media as an industry as well as a two-way form of communication in forming and maintaining relationships with audiences.